SITELLE: an Imaging Fourier Transform Spectrometer for the Canada–France–Hawaii Telescope. Issue 3 (8th March 2019) - Drissen, Laurent; Martin, Thomas; Rousseau-Nepton, Laurie; Robert, Carmelle; Martin, R Pierre; Baril, Marc; Prunet, Simon; Joncas, Gilles; Thibault, Simon; Brousseau, Denis; Mandar, Julie; Grandmont, Frédéric; et al.
Abstract: We present an overview of SITELLE, an Imaging Fourier Transform Spectrometer (iFTS) available at the 3.6-m Canada–France–Hawaii Telescope. SITELLE is a Michelson-type interferometer able to reconstruct the spectrum of every light source within its 11 arcmin field of view in filter-selected bands of the visible (350–900 nm). The spectral resolution can be adjusted up to R = 10 000 and the spatial resolution is seeing-limited and sampled at 0.32 arcsec pixel −1 . We describe the design of the instrument as well as the data reduction and analysis process. To illustrate SITELLE's capabilities, we present some of the data obtained during and since the 2015 August commissioning run. In particular, we demonstrate its ability to separate the components of the [O ii ] λλ 3726, 29 doublet in Orion and to reach R = 9500 around Hα; to detect diffuse emission at a level of 4 × 10 −17 erg cm −2 s −1 arcsec −2 ; to obtain integrated spectra of stellar absorption lines in galaxies despite the well-known multiplex disadvantage of the iFTS and to detect emission-line galaxies at different redshifts.